The prevalence of squamous cell carcinoma in different sites of oral cavity at our Rural Health Care Centre in Loni, Maharashtra – a retrospective 10-year study - Tandon, Parul; Dadhich, Anuj; Saluja, Harish; Bawane, Shilpa; Sachdeva, Shivani (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : Oral cancer ranks in the top three of all cancers in India and is quickly becoming a global health priority. More than 90% of oral and oropharyngeal cancers are squamous cell carcinoma. The purpose of this study was to document its incidence depending upon the involvement of different sites of oral cavity, and its variation with age and gender. Material and methods : Histopathologically proven oral squamous cell carcinoma cases were collected from the department of oral and maxillofacial surgery RDC, PIMS. The cases were systematically grouped under three headings: anatomical sub-site of oral cavity, age group, and gender, which were analysed to calculate the prevalence of oral cancer. The study was undertaken after obtaining approval from the institutional Ethical Committee board. Results : Among the different sites of oral cavity, the highest incidence (31.47%) of oral squamous cell carcinoma was seen for buccal mucosa in our study. The most affected age group (39.50%) were patients above 50 years old, predominantly involving males. Conclusions : The population in this study were mostly from remote areas, among which a high rate of occurrence of oral cancer was encountered because the people were of low socio-economic class, had a casual attitude towards their health, high rate of tobacco consumption, and limited health care facilities. This study provides valuable data of the prevalence of oral cancer among the rural population.